Gender differences in emotional intelligence : are you smart as you think emotionally - Lim, Tze Shin (2011)
The emotional intelligence (EQ) has been linked to positive aspects (e.g., self esteem, achievement, and psychological well-being) of an individual. Importance of gender differences in actual and self-perceived EQ level help to understand these aspects. The sample of this study comprised of 60 undergraduates’ students (30 males and 30 females) from University Tunku Abdul Rahman. By using stratified random sampling under probability sampling, Trait Emotional Intelligence Questionnaire-Short Form (TEIQueSF) and qualitative survey questions have been utilized to measure actual and selfperceived EQ level in gender. Findings indicated that there is no significant gender difference in actual and self-estimated EQ level. However, both genders perceived males have higher EQ level compared to females where seven main themes (emotionality, cognition/mentality, personality/characteristic, biology, self-control, culture/belief, and research findings) of explanation have been clinched. Discussion focuses on genders’ perception differences and future study on implications and corollaries of such thinking pattern should be investigated.